Preservative effects of the combined treatment of slightly acidic electrolyzed water and ice on pomfret - Huang, Xiaoling; Zhu, Songming; Zhou, Xiaomin; He, Jinsong; Yu, Yong; Ye, Zhangying (International Journal of Agricultural and Biological Engineering, 2021)
This study assessed the combined effect of slightly acidic electrolyzed water (SAEW) and slightly acidic electrolyzed water ice (SAEW-ice) on the quality of pomfrets over a period of 18 d of cold storage at 4°C. A presoak for 5 min in SAEW solution (22 mg/L) was used before the pomfrets were placed on SAEW-ice (pH: 6.45; ORP: 803 mV; ACC: 18 mg/L); The changes in physicochemical properties (i.e., pH, thiobarbituric acid, total volatile basic nitrogen and texture profile), microbial loads and sensory characteristics were all analyzed. Compared with the tap water (TW) group, the total bacterial counts of the SAEW group significantly decreased by 1.27 log10 CFU/g after immersion (p<0.05). The shelf life of the pomfrets was prolonged by 9 d by the combined treatment of SAEW and SAEW-ice during storage at 4°C. On the 18th day, the gumminess and chewiness values of the pomfrets in the SAEW+SAEW-ice group were 195 g and 3.97 mJ, respectively, which were significantly higher than those of the other groups (p<0.05). The results suggested that SAEW+SAEW-ice treatments have great potential as a novel method to maintain the quality and extend the shelf life of pomfrets during refrigerated storage.Keywords: pomfret, slightly acidic electrolyzed water, slightly acidic electrolyzed water ice, storage quality, preservationDOI: 10.25165/j.ijabe.20211401.5967Citation: Huang X L, Zhu S M, Zhou X M, He J S, Yu Y, Ye Z Y. Preservative effects of the combined treatment of slightly acidic electrolyzed water and ice on pomfret. Int J Agric & Biol Eng, 2020; 14(1): 230–236.